Effects of high dose sex pheromone on courtship, mating and oviposition of Chilo suppressalis (Walker) in the wind tunnel - GUO Qianshuang; CHEN Liling; SUI Hua; YANG Bin; ZHUO Fuyan; ZHU Xiaoming; GUO Rong; DU Yongjun (浙江大学学报. 农业与生命科学版, 2022)
To explore the courtship, mating and oviposition behavior of Chilo suppressalis (Walker) in a high dose sex pheromone environment, the mating disruption was simulated in a wind tunnel, and the sex pheromone titers were analyzed in combination with behavioral observation and chemical methods. The results showed that in the wind tunnel, the high dose of Z11-16:Ald and the ternary blend [m(Z11-16:Ald)∶ m(Z9-16:Ald)∶m(Z13-18:Ald)=10∶1∶1.2] of 3.1 mg per spraying significantly inhibited the mating rates and sex pheromone titers of female moths, but no significant differences were found between the two treatments. There were no significant differences in the number of mating pairs of male and female moths and the time interval between each spraying. The mating rates of male moths with the removal of antennae decreased to (8.3±1.1)% and (10.0±8.9)%, respectively, in the environment of spraying or not spraying high dose Z11-16:Ald. The number of laid eggs and egg hatching rates were not affected in the high dose sex pheromone environment. The ages of female moths significantly affected the mating rates with male moths. The mating rates of 1, 3 and 5 day-old female moths with 1 day-old male moths were (60.0±5.2)%, (31.7±6.0)%, and (8.3±3.1)%, respectively. The number of laid eggs and egg hatching rates of female moths decreased with the ages. In conclusion, the high dose sex pheromone Z11-16:Ald and complete blend can inhibit the mating rates and sex pheromone titers of C. suppressalis, and have no impact on the number of laid eggs and egg hatching rates of female moths, but the ages of female moths can affect the number of laid eggs and egg hatching rates; and the decrease in mating rates might be related to the inactivation of olfactory system of male moths.